Dialectics of social institute - Smirnov, Victor E. (Journal of the Belarusian State University. Sociology, 2019)
The dialectic of social institute as a system in which the permanent interaction of forms of human practical activity is carried out is considered. The typification of these forms creates in the public consciousness ideal view that cause the certain structure of organizational forms of human activity. The author’s definition of social institution, institution and organization is given in article. The dialectic of the social institute of different epochs is shown by the historical examples.
Keywords: social institution; organizations; institutions; dialectics; development; institutional changes; globalization; typification; habitatisation; contradiction; material production; productive forces